STRATEGI PENANGANAN PELAKU KEJAHATAN TERHADAP KESUSILAAN AGAR TIDAK MENJADI RESIDIVIS - Latifah Alkhairiyah; Mukhlis R; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
The large number of recidivist cases of crimes against morality that haveoccurred in Indonesia in recent years have raised concerns among the public.Based on data from the Directorate General of Corrections under the Ministry ofLaw and Human Rights in the last six years (2017-2022), there has been a verysignificant increase in the number of recidivist cases of crimes against moralityfrom year to year. The increase in recidivist cases shows that the handling andtraining for compensation for crimes against morality in Indonesia has not beeneffective enough in providing a deterrent effect to perpetrators of crimes againstmorality, so that perpetrators still dare to repeat crimes against morality. The aimof this thesis is firstly, to describe cases of recidivist crimes against morality andtheir current handling. Second, to develop strategies that can be implemented inhandling perpetrators of crimes against morality so that they do not becomerecidivists who commit crimes against morality.This research uses a normative juridical approach, where this researchfocuses on studying legal principles, especially the legal principle of the purposeof punishment, namely the legal principle of expediency in handling and trainingperpetrators of crimes against morality. The approach taken was to use qualitativedescriptive analysis techniques, in data collection the literature review methodwas used. The data sources used are primary and secondary legal materials.The conclusions obtained from the research results are first, based on thefacts and data found, there are still many shortcomings and defects in handlingperpetrators of crimes against morality, this is based on the increasing data onrecidivism cases of crimes against morality in Indonesia in the last six years, thehigh numbers reveal section in public spaces and even in schools, the rights andobligations of each compensation are the same and equal without consideringbecause the driver committed a criminal act. The latest solution from theGovernment is in the form of additional punishment of chemical castration, butuntil now it has not been implemented properly and correctly due to the manydynamics chemical castration punishment. Second, the strategy that researcherscan offer is to make improvements to the existing improvement training system inIndonesia. Researchers offer a solution in the form of holding specialpsychological and psychiatric rehabilitation facilities to lead criminals to decency.Where the development of psychological and mental health will be something thatis taken into consideration in freeing the perpetrator after the end of the prisonterm.Keywords: Strategy-Handling-decency-recidivism